Conversion of waste non-chrome metal complex tanned leather shavings to dual-functional bio-additive for the high-performance biomass-derived aldehyde tanned leather processing. (March 2022) - Ding, W.; Liu, H.; Hao, X.; Dong, L.; Pang, X.; Ding, Z.
Abstract: Waste collagen fiber (WCF) from non-chrome metal complex tanned leather shavings were converted to bio-additive (DCH) via catalytic peroxide oxidation for updating the performance of biomass-derived aldehyde (BAT) tanned chrome-free leather. The conversion degree of WCF was investigated, and four typical DCHs with different molecular weights (DCH-1: 19695 g/mol; DCH-2: 14942 g/mol; DCH-3: 8222 g/mol; DCH-4: 2959 g/mol), were selected for the post-tanning of BAT tanned leather. ICP-OES analysis indicated that DCH had similar metallic element content. FTIR showed that more carboxyl groups of DCH were formed as the decrease of its molecular weight (MW) due to the cleavage of peptide chains and de-tanning reaction, which was further verified by the decrease of isoelectric point (IEP) of DCH. During the post-tanning process, DCH had no obvious negative impacts on the overall uptake of post-tanning materials and the shrinkage temperature of leather, but it could perform a feasible filling effect. Besides, DCH could endow the crust leather with better dyeing uniformity, mechanical strengths, and organoleptic properties than commercial protein filler due to its special structure containing multivalent metal ions. This suggests that the as-prepared DCH has the capability for manufacturing high-performance chrome-free leather tanned by BAT. Graphical abstract: Image 1 Highlights: Waste collagen fiber (WCF) could be converted to bio-additive (DCH) via degradation. Conversion degree was close to 100%, almost achieving the complete recycling of WCF. DCH could be used in post-tanning of biomass-derived aldehyde (BAT) tanned leather. DCH could endow BAT crust leather with satisfactory dyeing uniformity. DCH could significantly update the mechanical strengths of BAT crust leather.